Motivation Drives Employee Performance through Insights from an Indonesian Study: Motivasi Mendorong Kinerja Karyawan melalui Wawasan dari Sebuah Studi di Indonesia - Aruni Izzatur; Lilik Indayani (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of career development, motivation, and the work environment on employee performance at the Al Falah Social Fund Foundation (YDSF) in Surabaya. Using a quantitative approach with regression analysis on data from 114 employees, the study found that intellectual ability and the non-physical work environment have positive but not significant effects on performance. In contrast, motivation has a significant positive effect. These findings highlight the importance of motivation in enhancing employee performance, suggesting that YDSF should prioritize motivational strategies to improve overall effectiveness. Highlights: 1. Motivation significantly boosts employee performance at YDSF.2. Intellectual ability, non-physical work environment show non-significant positive effects.3. Focus on motivational strategies to enhance performance. Keywords: career development, motivation, work environment, employee performance, YDSF